Geographical distribution of scrub typhus and risk of Orientia tsutsugamushi infection in Indonesia: Evidence mapping. - Kartika Saraswati; Ivo Elliott; Nicholas P J Day; J Kevin Baird; Stuart D Blacksell; Ristiyanto; Catherine L Moyes (Public Library of Science (PLoS), 2023)
Background Scrub typhus is a potentially fatal acute febrile illness caused by bacteria in the genus Orientia. Though cases have been documented, a comprehensive body of evidence has not previously been compiled to give an overview of scrub typhus in Indonesia. This study aimed to address this key knowledge gap by mapping and ranking geographic areas based on existing data on the presence or absence of the pathogen in humans, vectors, and host animals. Methodology/principal findings We performed searches on local and international electronic databases, websites, libraries, and collections including Embase, Medline, and Scopus to gather relevant evidence (including grey literature). After extracting data on the presence and absence of the pathogen and its vectors, we ranked the evidence based on the certainty for the presence of human infection risk. The country was divided into subnational units, and each were assigned a score based on the evidence available for that unit. We presented this in an evidence map. Orientia tsutsugamushi presence has been identified on all the main islands (Sumatra, Java, Borneo, Celebes, Papua). About two thirds of the data points were collected before 1946. South Sumatra and Biak had the strongest evidence for sustaining infectious vectors. There was only one laboratory confirmed case in a human identified but 2,780 probable cases were documented. The most common vector was Leptotrombidium deliense. Conclusions/significance Our review highlights the concerning lack of data on scrub typhus in Indonesia, the fourth most populous country in the world. The presence of seropositive samples, infected vectors and rodents confirm O. tsutsugamushi is widespread in Indonesia and likely to be causing significant morbidity and mortality. There is an urgent need to increase surveillance to better understand the burden of the disease across the archipelago and to inform national empirical fever treatment guidelines.